Nurse’s Experiences in Handling Stretcher Patients on Commercial Medical Escort in Indonesia: A Qualitative Study - Aditya, Ronal Surya; Yusuf, Ah; Solikhah, Fitriana Kurniasari; Kurniawan, Setyo Budi; Sheikh Abdullah, Siti Rozaimah (Bangladesh Journal of Medical Science, 2022)
Objective:The health system in Indonesia has a rapid development. Domestic and abroad medical escort services are currently becoming a trend. One of the medical escort services is a stretcher.This research was aimed to understand the experience of nurses in assisting patient in stretcherusingcommercialflights in Indonesia. Methods: Qualitative research is used in this research. Personal interviews are conducted for 3 months from August to October 2019on fifteen nurses who have authority to conduct stretcher patient assistance. All nurses were spread over 5 islands in Indonesia including Java, Sumatra, Kalimantan, Nusa Tenggara Barat and Bali. Interview transcripts were analyzed using qualitative content analysis. Results: Three themes with nine categories were emerged. Patient preparation and equipment,handling of patients on the plane, and hand over preparation are the obtained main themes from this study. Conclusion: The handling ofpatient in stretcher on commercial aviation hadseveral difficulties. Patient who are lying on 9-seats set airplane with nurses sitting across from patient made nurses must carefully prepare everything before take-off. Careful preparations will determine the safety of the patient on stretcher. In addition, nurses understand about the weather and mountainous changes that must be passed. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 502-511